Multisystem Inflammatory Syndrome in Children: Unique Disease or Part of the Kawasaki Disease Spectrum? - Matucci-Cerinic, Caterina; Caorsi, Roberta; Consolaro, Alessandro; Rosina, Silvia; Civino, Adele; Ravelli, Angelo (Frontiers in Pediatrics, 2021)
One of the most intriguing and mysterious phenomena observed during the COVID-19 pandemic has been represented by the occurrence of the multisystem inflammatory syndrome in children and adolescents (MIS-C). Patients with this condition have some overlapping signs and symptoms with those of Kawasaki disease (KD), but also display clinical features that are uncommon or less frequent in this illness, such as diarrhea, abdominal pain and myocardial involvement. The sickest patients may develop multiorgan failure and shock, usually due to myocarditis. Management is based on the administration of intravenous immunoglobulin, glucocorticoids and, in the most severe instances, anakinra. It is still debated whether MIS-C and KD represent different illnesses or are part of the same disease spectrum. The aim of the present review is to analyze critically the evidence in favor of the latter hypothesis and to provide the authors’ personal interpretation of the relationship between the two conditions.